2017
DOI: 10.1016/j.stem.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Nup153 Interacts with Sox2 to Enable Bimodal Gene Regulation and Maintenance of Neural Progenitor Cells

Abstract: Neural progenitor cells (NeuPCs) possess a unique nuclear architecture that changes during differentiation. Nucleoporins are linked with cell-type-specific gene regulation, coupling physical changes in nuclear structure to transcriptional output; but, whether and how they coordinate with key fate-determining transcription factors is unclear. Here we show that the nucleoporin Nup153 interacts with Sox2 in adult NeuPCs, where it is indispensable for their maintenance and controls neuronal differentiation. Genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
131
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(141 citation statements)
references
References 60 publications
(86 reference statements)
10
131
0
Order By: Relevance
“…Jacinto et al [5] then reported a role for the nucleoporin Nup153, which localizes to the nuclear basket and also exists outside of the pore in the nucleoplasm, in the regulation of ESC pluripotency. These observations were recently confirmed by Toda et al, [6] who further showed that neuroprogenitor cells require high expression of Nup153 for their maintenance. These observations were recently confirmed by Toda et al, [6] who further showed that neuroprogenitor cells require high expression of Nup153 for their maintenance.…”
supporting
confidence: 60%
See 3 more Smart Citations
“…Jacinto et al [5] then reported a role for the nucleoporin Nup153, which localizes to the nuclear basket and also exists outside of the pore in the nucleoplasm, in the regulation of ESC pluripotency. These observations were recently confirmed by Toda et al, [6] who further showed that neuroprogenitor cells require high expression of Nup153 for their maintenance. These observations were recently confirmed by Toda et al, [6] who further showed that neuroprogenitor cells require high expression of Nup153 for their maintenance.…”
supporting
confidence: 60%
“…Reduction of Nup153 expression in ESCs was shown to induce early neuronal differentiation, revealing a role for this nucleoporin in maintaining ESC stemness [5]. These observations were recently confirmed by Toda et al, [6] who further showed that neuroprogenitor cells require high expression of Nup153 for their maintenance.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Mouse NPCs were obtained from embryonic female C57BL/6 mouse hippocampus and cultured as described previously (Toda et al, 2017). NPCs were cultured in DMEM/F-12 supplemented with N2 and B27 (Invitrogen) in the presence of FGF2 (20 ng/ml), EGF (20 ng/ml), laminin (1 μg/ml) and heparin (5 μg/ml), using poly-ornithine/laminin (Sigma)-coated plastic plates.…”
Section: Cell Culturementioning
confidence: 99%